Delayed Puberty in Girls with Primary Amenorrhea: A Report of Cases - Fatinah Shahab; Inu Mulyantoro; Hary Tjahjanto; Tri Indah Winarni; Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2021)
Background:Female puberty starts when the pituitary hormone producing follicle-stimulating hormone (FSH) and luteinizing hormone (LH), which will stimulate the ovaries to produce estrogen. Delayed puberty with primary amenorrhea in female is the lack of breast development followed by the absence of menses 3 years after the initiation of breast development. Sex chromosomes have an important role in determining the sex, germ cell differentiation of foetus, and reproductive functions of an offspring, thus, sex chromosomal aberrations frequently cause primary amenorrheaCase presentation: We report two delayed puberty cases with the chief complain of primary amenorrhea. Both cases showed hypoplasia of uterus and ovaries on pelvic imaging and hormonal assay showed low of FSH. The first case was gonadal dysgenesis with 46,XX karyotype and low level of estrogen and the second case was a turner syndrome with 45,X karyotype and normal level of estrogen. Conclusion:This study reported delayed puberty with primary amenorrhea cases due to different chromosomal aberration pattern which have similar clinical features. Therefore, cytogenetic examination is needed for any primary amenorrhea cases in order to accomplish the confirmatory diagnosis and for the clinicians to make a correct intervention and treatment.